The Need for Standards in Evaluating the Quality of Electronic Health Records and Dental Records: A Narrative Review - Varadraj P. Gurupur; Giang Vu; Veena Mayya; Christian King (Big Data and Cognitive Computing)
Over the past two decades, there has been an enormous growth in the utilization of electronic health records (EHRs). However, the adoption and use of EHRs vary widely across countries, healthcare systems, and individual facilities. This variance poses several challenges for seamless communication between systems, leading to unintended consequences. In this article, we outline the primary factors and issues arising from the absence of standards in EHRs and dental record implementation, underscoring the need for global standards in this area. We delve into various scenarios and concepts that emphasize the necessity of global standards for healthcare systems. Additionally, we explore the adverse outcomes stemming from the absence of standards, as well as the missed opportunities within the healthcare ecosystem. Our discussions provide key insights on the impacts of the lack of standardization.